Four-factor prothrombin complex concentrate is associated with improved survival in trauma-related hemorrhage: A nationwide propensity-matched analysis. Issue 2 (August 2019) - Zeeshan, Muhammad; Hamidi, Mohammad; Feinstein, Ara J.; Gries, Lynn; Jehan, Faisal; Sakran, Joseph; Northcutt, Ashley; O'Keeffe, Terence; Kulvatunyou, Narong; Joseph, Bellal
Abstract : INTRODUCTION: Post-traumatic hemorrhage is the most common preventable cause of death in trauma. Numerous small single-center studies have shown the superiority of four-factor prothrombin complex concentrate (4-PCC) along with fresh frozen plasma (FFP) over FFP alone in resuscitation of trauma patients. The aim of our study was to evaluate outcomes of severely injured trauma patients who received 4-PCC + FFP compared to FPP alone. METHODS: Two-year (2015–2016) analysis of the American College of Surgeons-Trauma Quality Improvement Program database. All adult (age ≥18 years) trauma patients who received 4-PCC + FFP or FFP alone were included. We excluded patients who were on preinjury anticoagulants. Patients were stratified into two groups: 4-PCC + FFP versus FFP alone and were matched in a 1:1 ratio using propensity score matching for demographics, vitals, injury parameters, comorbidities, and level of trauma centers. Outcome measures were packed red blood cells, plasma and platelets transfused, complications, and mortality. RESULTS: A total of 468 patients (4-PCC + FFP, 234; FFP alone, 234) were matched. Mean age was 50 ± 21 years; 70% were males; median injury severity score was 27 [20–36], and 86% had blunt injuries. Four-PCC + FFP was associated with a decreased requirement for packed red blood cells (6 units vs. 10 units; p = 0.02) and FFP (3 units vs. 6 units; p = 0.01) transfusion compared to FFP alone. Patients who received 4-PCC + FFP had a lower mortality (17.5% vs. 27.7%, p = 0.01) and lower rates of acute respiratory distress syndrome (1.3% vs. 4.7%, p = 0.04) and acute kidney injury (2.1% vs. 7.3%, p = 0.01). There was no difference in the rates of deep venous thrombosis ( p = 0.11) and pulmonary embolism ( p = 0.33), adverse discharge disposition ( p = 0.21), and platelets transfusion ( p = 0.72) between the two groups. CONCLUSIONS: Our study demonstrates that the use of 4-PCC as an adjunct to FFP is associated with improved survival and reduction in transfusion requirements compared to FFP alone in resuscitation of severely injured trauma patients. Further studies are required to evaluate the role of addition of PCC to the massive transfusion protocol. LEVEL OF EVIDENCE: Therapeutic studies, level III. Abstract : Supplemental digital content is available in the text.